Performance Optimization through Work Motivation - Zailani Sinaga, Muhammad; B, Mesra (Proceedings of the International Conference on Multidisciplinary Science (INTISARI), 2024)
Today, a company's ability to successfully navigate the highly competitive advantage landscape depends solely on its ability to organize and manage its human resources effectively. Working with clear goals and organizational strategy linkages will result in human resource performance. So, performance is about what is done and how the work is done, as well as how the work is done and the results obtained from it. The results of this research are as follows; Organizational culture has a positive and insignificant effect on employee performance with the original sample of 0.054 and a p value of 0.293. Organizational culture has a positive and significant effect on work motivation with an original sample value of 0.606 and a p value of 0.000. Organizational climate has a positive and significant effect on employee performance with an original sample value of 0.137 and p-values of 0.039. Organizational climate has a positive and significant effect on work motivation with an original sample value of 0.222 and a p value of 0.003. Work Motivation has a positive and significant effect on Employee Performance with an original sample value of 0.779 and a p value of 0.000. Organizational culture has a positive and significant effect on employee performance through work motivation indirectly with an original sample value of 0.472 and a p value of 0.000. Organizational climate has a positive and significant effect on employee performance through work motivation indirectly with an original sample value of 0.173 and a p value of 0.003.